Sorong Serah Aji Krame in the Novel Merpati Kembar di Lombok by Nuriadi - Lisa Rosalia; Nuriadi; Aswandikari; Saharudin; Ahmad Sirulhaq (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study aims to analyze how the Sorong Serah Aji Krame tradition is represented in Nuriadi’s novel Merpati Kembar di Lombok and compare it with its actual implementation in South Montong Baan Village. The research findings indicate that in the MKL novel, the author narrates the Sorong Serah Aji Krame ceremony using the term "serah doe/ngadep," without providing detailed explanation of its procession. However, in several sections, such as the preparation of the pembayun and the depiction of the pembayun chanting process, brief descriptions are offered. Conversely, in actual practice in South Montong Baan Village, the ceremony exhibits genuine complexity comprising the delegation of pisolo (emissary), religious greetings, customary greetings, the main ceremony, the pronouncement of aji krame (dowry), the handover of aji krame, the cutting of the Jinnah rope, and the closing ceremony. Meanwhile, several cultural symbolic meanings are embedded within the tradition, encompassing values of politeness, spirituality, honesty, and transparency.